1980
DOI: 10.1136/jcp.33.9.836
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of Mycoplasma pneumoniae infection by enzyme immunoassay.

Abstract: SUMMARY Antibodies against Mycoplasma pneumoniae antigen obtained by Tween-ether treatment from purified M. pneumoniae were measured by means of enzyme-linked immunosorbent assay (ELISA). Paired sera from 19 patients with pneumonia and from 13 patients with acute pancreatitis with a significant rise in complement fixing antibodies against M. pneumoniae were studied. Single sera from healthy 1-year-old children were used as controls. High levels of IgG and IgM class antibodies were seen in sera from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The stronger IgM reaction observed by EIA-Sorin and EIA-Biotest, in our study, is probably due to either nonspecific binding of macroglobulins or low levels of cross-reacting antibodies binding to nonprotein constituents of the EIA antigen preparation (3,19,26). Because it has been previously demonstrated that the main antigenic components reacting are proteins, better-defined specific protein antigen preparations should give more-accurate results and should be more specific than the use of a glycolipid or whole-cell antigen (8,14,27). However, other work proposed viability for a glycolipid antigen-based EIA with chloroform-methanol extraction (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stronger IgM reaction observed by EIA-Sorin and EIA-Biotest, in our study, is probably due to either nonspecific binding of macroglobulins or low levels of cross-reacting antibodies binding to nonprotein constituents of the EIA antigen preparation (3,19,26). Because it has been previously demonstrated that the main antigenic components reacting are proteins, better-defined specific protein antigen preparations should give more-accurate results and should be more specific than the use of a glycolipid or whole-cell antigen (8,14,27). However, other work proposed viability for a glycolipid antigen-based EIA with chloroform-methanol extraction (17).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional complement fixation test (CFT) using a glycolipid antigen gives unspecific reactions and lacks sensitivity (16,19). Alternative tests have recently been developed to obtain moreaccurate and prompt diagnosis: indirect enzyme immunoassay (EIA) measuring separately immunoglobulin G (IgG) and IgM class antibodies (8,14,27,33,35) and PCR for rapid and sensitive detection of M. pneumoniae in respiratory tract specimens (1,4,6,31,32,36). The objective of this retrospective study was to compare the performance of four commercially available EIAs for the detection of specific M. pneumoniae IgG and IgM antibodies in assessing the antibody response of suspected M. pneumoniae patients on the basis of PCR-positive results for M. pneumoniae in respiratory samples.…”
mentioning
confidence: 99%
“…antibody in a single serum sample or by significant rise in antibody titer in paired serum samples obtained during the acute and convalescent stages of the disease. Recently, ELISA has been accepted for serodiagnosis of M. pneumoniae infection (4,5,7,19,23,24). In the ELISA, as single serum dilution of 1: 100 has been most often used, the interpretation of the results is often difficult due to background readings.…”
Section: Western Blot Analysis Of Sera Of Patients Infected With M Pmentioning
confidence: 99%
“…These results suggested the existence of cross-reactive antibodies to mycoplasmas in human sera. Cross-reactive antibodies to M. pneumoniae and other mycoplasmas in the patients' sera were also demonstrated by Western blotting technique.The enzyme-linked immunosorbent assay (ELISA) has been used for routine serological diagnosis of Mycoplasma pneumoniae infection because of its high sensitivity and simplicity (4,5,7,19,23,24). But, as high background readings are often observed in the ELISA, the interpretation is often very difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation